Phase change mediated mechanically transformative dynamic gel for intelligent control of versatile devices - Zhao, Xing; Peng, Li-Mei; Chen, Yi; Zha, Xiang-Jun; Li, Wu-Di; Bai, Lu; Ke, Kai; Bao, Rui-Ying; Yang, Ming-Bo; Yang, Wei (Materials horizons, 2021)
Traditional devices, including conventional rigid electronics and machines, as well as emerging wearable electronics and soft robotics, almost all have a single mechanical state for particular service purposes. Nonetheless, dynamic materials with interchangeable mechanical states, which enable more diverse and versatile applications, are urgently necessary for intelligent and adaptive application cases in the future electronic and robot fields. Here, we report a gel-like material composed of a crosslinking polymer network impregnated with a phase changing molten liquid, which undergoes an exceptional stiffness transition in response to a thermal stimulus. Vice versa , the material switches from a soft gel state to a rigid solid state with a dramatic stiffness change of 10 5 times (601 MPa versus 4.5 kPa) benefiting from the liquid-solid phase change of the crystalline polymer once cooled. Such reversibility of the phase and mechanical transition upon thermal stimuli enables the dynamic gel mechanical transformation, demonstrating potential applications in an adhesive thermal interface gasket (TIG) to facilitate thermal transport, a high-temperature warning sensor and an intelligent gripper. Overall, this dynamic gel with a tunable stiffness change paves a new way to design and fabricate adaptive smart materials toward intelligent control of versatile devices. A phase change mediated mechanically transformative dynamic gel enables dramatic stiffness change under a heat stimulus for intelligent control of versatile devices.